Variability Survey of Southern Open Clusters NGC 6134, NGC 6416, Collinder 394, and Alessi 10 - Mandey, Denny; Ramadhan, Dhimaz Gilang; Yusuf, Muhammad; Perhati, Teduh; Ramadhan, Sahlan; Pramono, Theofilus Hobba; Anin, Chornelis J’Be; Premadi, Premana Wardayanti; Jaelani, Anton Timur; Jatmiko, Agus Triono Puri; Arifyanto, Mochamad Ikbal (Directorate for Research and Community Services (LPPM) ITB, 2026)
We present the results of a brightness variability survey of four southern open clusters, namely NGC 6134, NGC 6416, Collinder 394, and Alessi 10, which were observed using three telescopes following a time series photometric scheme during the dry season in 2022. The purpose of these observations was to detect variability events and their types of variability in star members of these four clusters. Data analysis was performed using a differential photometry method to produce light curves. Several new variable star candidates were discovered in the observed clusters. More observational data are needed to examine the consistency of the variabilities, estimate relevant periodicity, and determine the type of variable star.